Optimized Weight Point ADF using SOS Algorithm - Gayatri Mohapatra; Manoj Kumar Debnath (IAES Indonesian Section, 2022)
Active dc filter (ADF) has become the most viable alternatives for the compensation of the harmonics in the power system analysis. These filters are capable enough to minimize the total harmonic distortion (THD) and provide compensation towards the power quality issues appearing in the transmission system. A simulated model of a HVDC system is designed in MATLAB and the disturbance is injected in the form of load change and the controller efficacy is checked. This paper basically deals with the operational characteristics of the active filter for specific voltage rating irrespective of load and used to reduce harmonics present in the output voltage of the HVDC converter when cascaded with the inverter. The gains of the ADF are optimized with Symbiotic Organism Search Optimization (SOS) with THD as a constraint.